2021
DOI: 10.1590/s1983-41952021000500010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Carbon Nanotubes (CNTs) aspect ratio on the rheology, thermal conductivity and mechanical performance of Portland cement paste

Abstract: Carbon nanotubes (CNTs) are potential candidates to enhance the heat balance of concrete, reducing internal stresses caused by differential heating in massive concrete elements. The higher the aspect ratio (AR) and content of CNTs, the greater the expected thermal conductivity (TC). However, high AR may impair the proper dispersion of CNTs in cementitious matrix, potentially harming the workability and mechanical strength of the composite. This work evaluated the effect of the AR (35, 250, 900, and 3500) and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 55 publications
1
9
0
Order By: Relevance
“…These results agree with those reported by Du et al [20], who observed increases in the thermal conductivity of geopolymer-SiC composites and this was expected since SiC whiskers are excellent heat conductors [20,42]. Similar results were also reported for the cementitious matrix reinforced with carbon nanotubes [43]. The higher increases in thermal conductivity with the addition of 500-NWs compared with NT-NWs are probably due to the higher surface area of the former.…”
Section: Hardened-state Propertiessupporting
confidence: 92%
“…These results agree with those reported by Du et al [20], who observed increases in the thermal conductivity of geopolymer-SiC composites and this was expected since SiC whiskers are excellent heat conductors [20,42]. Similar results were also reported for the cementitious matrix reinforced with carbon nanotubes [43]. The higher increases in thermal conductivity with the addition of 500-NWs compared with NT-NWs are probably due to the higher surface area of the former.…”
Section: Hardened-state Propertiessupporting
confidence: 92%
“…Longer CNT particles are more uniformly aligned in the fluid and create continuous pathways for heat conduction [81]. However, in some literature, the effect of aspect ratio on thermal conductivity is not guaranteed [82].…”
Section: Aspect Ratiomentioning
confidence: 99%
“…Fewer studies of composites were found for electrical conductivity, and none were found for thermal conductivity, using the criterion of a pristine MWCNT control sample. It is known that the thermal conductivity of cementitious composites improves with the addition of nanotubes [ 12 , 81 , 87 ] for both pristine and functionalized MWCNTs.…”
Section: Electrical and Thermal Conductivity Of Cementitious Composit...mentioning
confidence: 99%
“…Thermal conductivity of cementitious composites improves on the addition of nanotubes [ 12 , 81 , 87 ]. To the authors’ knowledge, there are no studies where the thermal conductivity of cementitious composites was compared for bare and functionalized MWCNTs.…”
Section: Electrical and Thermal Conductivity Of Cementitious Composit...mentioning
confidence: 99%